PERBANDINGAN LATAR BELAKANG FILOSOFIS KONSEP KEKELUARGAAN DALAM SISTEM SOSIAL JAWA DAN SISTEM KENEGARAAN INDONESIA - Sudaryanto, . (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2009)
AbstractJavanese take care of harmony and honour of their homeland as important as they take care of their family. Familiarity does not only occur in their family, but also in the wide society. Their society is considered as a big family and viewed as a harmonywhich requires to be taken care of. The harmonious life does not merely take care of an orderly social relationship, but it also respects and relates to supernatural realm. According to Javanese, the human life on the earth is directly interconnected with the supernatural realm.The modern state of Indonesia applies a social system of familiarity which is based on harmonious values and mutualassistance (mutuality) and reciprocity. The values exist on the social system of Java. However, there is an elementaryphilosophical difference. The philosophy of modern Indonesia state views that the familiarity, which includes harmonious values, mutual assistance and reciprocity, only occurs between state and citizen, not the supernatural realm.Keyword: familiarity, respect, harmony, mutuality, reciprocity.